2015
DOI: 10.15252/emmm.201404524
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E promotes subretinal mononuclear phagocyte survival and chronic inflammation in age‐related macular degeneration

Abstract: Physiologically, the retinal pigment epithelium (RPE) expresses immunosuppressive signals such as FAS ligand (FASL), which prevents the accumulation of leukocytes in the subretinal space. Age-related macular degeneration (AMD) is associated with a breakdown of the subretinal immunosuppressive environment and chronic accumulation of mononuclear phagocytes (MPs). We show that subretinal MPs in AMD patients accumulate on the RPE and express high levels of APOE. MPs of Cx3cr1−/− mice that develop MP accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
155
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(166 citation statements)
references
References 69 publications
4
155
0
5
Order By: Relevance
“…To test whether a more AMD‐relevant Mo stimulation induces a similar resistance to elimination, we added apolipoprotein E (APOE) to the coculture system. We previously showed that APOE, which is observed in subretinal MPs of AMD patients (Levy et al ., ) and in MPs that express the AMD‐risk isoform APOE2 (Levy et al ., ), activates the CD14/TLR2/4‐dependent innate immunity receptor cluster and induces inflammatory cytokines (Levy et al ., ,b). Similar to LPS, recombinant APOE (but not heat‐inactivated APOE, data not shown) induced a robust increase in Mo numbers in coculture with hiRPE but not with hFibro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether a more AMD‐relevant Mo stimulation induces a similar resistance to elimination, we added apolipoprotein E (APOE) to the coculture system. We previously showed that APOE, which is observed in subretinal MPs of AMD patients (Levy et al ., ) and in MPs that express the AMD‐risk isoform APOE2 (Levy et al ., ), activates the CD14/TLR2/4‐dependent innate immunity receptor cluster and induces inflammatory cytokines (Levy et al ., ,b). Similar to LPS, recombinant APOE (but not heat‐inactivated APOE, data not shown) induced a robust increase in Mo numbers in coculture with hiRPE but not with hFibro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic administration of the anti‐IL‐6R monoclonal antibody MR16‐1 effectively suppressed the expression of CCL2 and VEGF and reduced macrophage infiltration as well as the CNV area (Izumi‐Nagai et al, ). IL‐6 is known to repress Fas ligand expression in the RPE, which then leads to impaired clearance and accumulation of MPs in the subretinal space (Levy et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…Microglial cells, the resident immune cells of the CNS, play a key role in the initiation and perpetuation of chronic inflammatory events in the aging retina (Sierra et al , ; Damani et al , ). Furthermore, mononuclear phagocyte reactivity associated with subretinal migration is a common hallmark in human AMD and related mouse models (Gupta et al , ; Combadière et al , ; Levy et al , ). Consequently, signaling pathways and molecular targets that modulate microglia and macrophage activity represent attractive therapeutic tools for the treatment of degenerative and inflammatory diseases of the retina, including AMD (Langmann, ).…”
Section: Introductionmentioning
confidence: 99%